Chlorodifluoroacetyl azide, ClF 2CC(O)N 3: Preparation, properties, and decomposition - Ramos Guerrero, Luis Alejandro (2012)
Chlorodifluoroacetyl azide, ClF 2CC(O)N 3, was prepared and characterized by IR (gas, Ar matrix), Raman (liquid), UV-vis (gas), and 19F, 13C NMR spectroscopy. The vibrational spectra were analyzed in terms of a single conformer, gauche-syn, where the Cl-C and the N α=N β bonds are gauche and syn to the C=O bond, respectively. The photo and thermal decomposition reactions of the azide were studied with the aid of matrix isolation. In both cases, a new isocyanate species ClF 2CNCO was produced and characterized by matrix IR spectroscopy. The conformational properties and the Curtius rearrangement pathways of this new carbonyl azide were theoretically explored, which suggest the preference of a concerted over stepwise decomposition for the global minimum gauche-syn conformer.